PENGEMBANGAN ALAT PERAGA PEMBELAJARAN BERBASIS TEKNOLOGI MURAH MATERI RADIASI KALOR DAN TEKANAN HIDROSTATIK - Dewi, Siska; Hakim, Lucky Maulana (Universitas Mandiri, 2024)
This study aims to develop low-cost technology-based learning aids in physics, specifically on heat radiation, using Student Worksheets (LKS). The Suyanto method of research and instructional media development was employed, including internal testing and variance similarity testing of the learning aids. The results consist of physics learning aids and LKS that have been internally validated, in line with theoretical expectations. The LKS validation yielded a score of 3.14, indicating suitability for use, while the external test using a One-Shot Case Study showed a student learning outcome score of 3.61, signifying good learning quality. Assessment of the appeal of the learning aids and LKS yielded a score of 3.32, and ease of use scored 3.17, indicating positive reception. Improvements were made before the production stage, which only involved prototyping.